Task Force: Connecting India, China and Southeast Asia - New socio-economic developments - Anja Senz; Dieter Reinhardt (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2014)
The border regions between Northeast India, Bangladesh, Myanmar and Southwest China are characterized by close historical, intra-ethnic relations and a developing civil society sector as well as violent conflicts and disputes about hydropower and resource extraction projects. What is more, this region will be affected by climate change. The articles reflect expanding regional economic relations, resource extraction projects, climate change challenges, minority issues and the potential for further involvement of the civil society. – – Die Grenzregionen zwischen Nordostindien, Myanmar und Südwestchina sind geprägt von engen historischen, intra-ethnischen Beziehungen, von einer sich entwickelnden Zivilgesellschaft sowie von Gewaltkonflikten und Konflikten über Wasserkraft- und Ressourcengewinnungsprojekte. Diese Region wird zudem vom Klimawandel betroffen sein. Die Aufsätze behandeln die wachsenden regionalen Wirtschaftsverbindungen, Ressourcenerschließungsprojekte, Herausforderungen des Klimaschutzes, Minderheitenfragen sowie Möglichkeiten des zivilgesellschaftlichen Engagements.
Keywords: 330; India; Northeast India; Myanmar; Yunnan; China; ethnic minorities; economic development; hydropower; resources; climate change